Chapter Lingua di genere, inclusione, lingua pubblica: spunti di riflessione in punta di langue e di parole - Biffi, Marco (Proceedings e report, 2023)
This contribution proposes some general observations on gendered language in a public context. Some specific issues are discussed: 1) language can be neither the only nor the main tool for a truly inclusive society, for which it is rather necessary to raise the level of average culture; 2) the public language has to refer to standard Italian in order to guarantee transparency for all citizens (even of those who do not have a high level of linguistic competence and therefore cannot handle exogenous changes in structure) 3) the unmarked masculine in certain contexts is however an inclusive strategy that in Italian is embedded in an articulated system of solutions that are not always based on the grammatical masculine (such as the use of feminine persona).